Definition of radial movements of cylindrical covers of capacities of fire trucks - Kulakovskiy Борис; Martynenko Тарас; Mendelev Валерий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2014)
The comparative analysis of weight and dimensional parameters (height of the center of gravity, weight and the square of surfaces of walls at unit of volume of liquid, cross stability against capsizing) tanks of cylindrical and rectangular forms is made. With application of the general theory of thin covers settlement formulas by determination of tension and deflections of a momentless cylindrical cover of any cross section are received.